Demographic Analysis and Lipid profile in Fibromyalgia Syndrome - Farid, Lubna M.; Turki, Kismat M.; Al-Osami, Mohammed H. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Fibromyalgia syndrome (FMS) is a very common cause of multiple regional musculoskeletal (MSK) pain and disability; it is characterized by chronic widespread for at least three months and tender points identified by the American Collage of Rheumatology (ACR).The cause of FMS is currently unknown. However, several hypotheses have been developed including genetic predisposition. This study aims to evaluate the contribution of serum lipid profile to the pathophysiology of FMS. Patients & Methods: The study has included 160 patients with FMS with age range (18-72) years and 60 control individuals who were age and sex matching with FMS patients: 29 patients with chronic musculoskeletal complaints but without FMS and 31 healthy controls. Colorimetric method was used to determine serum lipid profile. Results were evaluated using descriptive and inferential statistics; data were expressed as (mean ± SEM). P value of <0.05 was accepted as significant. Results: There were no significant differences among the three subject groups in serum lipid profile. Conclusion: Lipid profile has no role in FMS patients as a cause or result of this syndrome.